Strategi Raya Negara Tradisional di Nusa Tenggara: Tinjauan Sejarah - Hariyono, Hariyono; Wijaya, Daya Negri; Wahyudi, Deny Yudo (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2025)
This article aims to analyze the political and governmental strategies implemented by traditional states in Nusa Tenggara in dealing with internal and external dynamics in the past. This study discusses the patterns of adaptation and political maneuvers carried out by local kingdoms such as Larantuka and Lombok in maintaining sovereignty, while managing relations with external powers, including European colonialism and regional trade networks. The approach used is historical-critical to identify the strategies applied in military power, diplomacy, strategic alliances, and traditional bureaucratic reforms to enhance the effectiveness of governance. The f indings reveal that cultural adaptability and the utilization of local resources are key factors in the success of traditional states in the archipelago. The contribution of this study is providing an understanding of regional political history and its relevance in the context of managing local autonomy today.